Neither fascism nor democracy*: Contre-Attaque redux - Bolt Rasmussen, Mikkel (Peripeti, 2023)
The article presents and discusses André Breton and Georges Bataille’s Contré Attaque project in the mid-1930s where the two Surrealists sought to find a position that was both critical towards the emerging fascist movements, a Stalinized Communist Party and a crisis-ridden liberal democracy. The brief experiment will be used in an analysis of the new contemporary fascist tendencies that have been appearing during the last ten years in the West.